2015
DOI: 10.1016/j.surg.2015.03.034
|View full text |Cite
|
Sign up to set email alerts
|

Calpain inhibition decreases myocardial apoptosis in a swine model of chronic myocardial ischemia

Abstract: Introduction Calpain is a family of cysteine proteases that has an important role in the initiation, regulation and execution of cell death. Our recent studies using a hypercholesterolemic swine model demonstrated that in the setting of metabolic syndrome calpain inhibition improved collateral dependent perfusion, and increased expression of proteins implicated in angiogenesis and vasodilation. In this study, we hypothesized that calpain inhibition (CI) would decrease myocardial apoptosis in the same model. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 20 publications
(31 reference statements)
1
27
0
Order By: Relevance
“…These risk factors include (1) greater weight gain, (2) higher total cholesterol and low‐density lipoprotein/HDL ratios, (3) increased mean arterial pressure, and (4) elevated blood glucose levels in response to a glucose tolerance test 10. Using this model, we found that moderate inhibition of calpain decreases myocardial apoptosis, improves collateral dependent perfusion, and increases expression of signaling proteins that promote angiogenesis 11, 12. Interestingly, GSK‐3β is a substrate for calpain.…”
Section: Introductionmentioning
confidence: 95%
“…These risk factors include (1) greater weight gain, (2) higher total cholesterol and low‐density lipoprotein/HDL ratios, (3) increased mean arterial pressure, and (4) elevated blood glucose levels in response to a glucose tolerance test 10. Using this model, we found that moderate inhibition of calpain decreases myocardial apoptosis, improves collateral dependent perfusion, and increases expression of signaling proteins that promote angiogenesis 11, 12. Interestingly, GSK‐3β is a substrate for calpain.…”
Section: Introductionmentioning
confidence: 95%
“…Twenty‐three Yorkshire swine (Tufts, Boston, MA) underwent placement of an ameroid constrictor to their left circumflex artery at 11 weeks of age, in a manner similar to that previously reported13, 14, 15 (Figure 1). Pigs received aspirin (10 mg/kg) 1 day before surgery and 5 days postoperatively.…”
Section: Methodsmentioning
confidence: 94%
“…The data, analytic methods, and study materials have been and will continue to be made available to other researchers for purposes of reproducing the results or replicating the procedure 13, 14, 15, 16, 17, 18, 19, 20…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, Ca 2+ can stimulate calpain, a cysteine protease which can cleave Bax, creating pro-apoptotic fragments [90]. …”
Section: Cardiomyocyte Death In Hfmentioning
confidence: 99%